The Politics of Black Joy Zora Neale Hurston and Neo-Abolitionism - Stewart, Lindsey (Northwestern University Press, 2021)
In the antebellum period, slave owners weaponized southern Black joy to argue for enslavement while abolitionists wielded sorrow by emphasizing racial oppression. Both arguments were so effective that a political uneasiness on the subject still lingers. Lindsey Stewart wades into these uncomfortable waters by developing Zora Neale Hurston's contributions to political theory and philosophy of race by introducing the politics of joy as a refusal of neo-abolitionism, a political tradition that reduces southern Black life to tragedy or social death. Zora Neale Hurston's essays, Beyoncé's Lemonade, and figures including Frederick Douglass, W.E.B. Du Bois, Toni Morrison, Angela Davis, Saidiya Hartman, Imani Perry, Eddie Glaude, and Audra Simpson offer crucial insights and new paths for our moment. Examining popular conceptions of Black political agency at the intersection of geography, gender, class, and Black spirituality, The Politics of Black Joy is essential reading.